Trapped, Released, Transformed: How Minerals Shape the Cycling of Organic Matter in Soils - Konrad, Alexander; Justus Liebig University Giessen (My University, 2025)
Soil organic carbon persistence arises from the intertwined effects of mineral surfaces, microbial activity, and the chemical structure of organic matter, which is further modulated by a soil´s boundary conditions. This dissertation addresses two linked questions: How do minerals govern soil organic matter adsorption and desorption, and how do these organo-mineral interactions feed back on microbial utilization and persistence of mineral-associated organic carbon? To probe these questions, calorimetry was combined with isotope tracing and mineral long-term field exposure studies. Isothermal titration calorimetry provided the first direct thermodynamic quantification of adsorption of organic acids to mineral surface, showing that salicylic acid and citric acids bind exothermically to goethite. Calorimetry adsorption experiments onto goethite with differing lattice defect densities uncovered intensified exothermic binding and a greater loss of entropy on minerals abundant with defects, highlighting that adsorption thermodynamics can differ even for a single mineral type substantially. To connect mineral control of organic matter sorption with its microbial fate, uniformly and carboxyl-radiocarbon labeled monomers were adsorbed onto kaolinite, illite and goethite in a set of batch sorption experiments and incubated in loamy and sandy arable topsoil. Despite strong inner-sphere complexation, a substantial share of ligand-bound carboxyl carbon was mineralized. At the molecular scale, microbial carbon use efficiency (CUE) of mineral-adsorbed monomers rose linearly with desorbability (i.e., the ratio of the amount desorbed to the amount sorbed) across all investigated compounds. Notably, CUE values were consistently lower for monomers bound to goethite than to the clay minerals. Taken together, these findings show that mineral surface properties and sorption-desorption dynamics can redirect metabolic allocation between biomass synthesis and respiratory loss. Recognizing that minerals alter nutrient availability in soil, the dissertations research extended to cover phosphorus dynamics as well. In incubation studies, goethite-amended soil´s strong immobilization of phosphate constrained microbial growth, which channeled metabolism toward higher respiration and lower CUE, while illite did not immobilize phosphorus, resulting in higher CUEs for mineral-adsorbed monomers. Conversely, studying phosphorus transport in forest ecosystems exposed that soil colloids rich in carbon and iron can deliver large quantities of bioavailable phosphorus into sinks mimicking plant roots. This demonstrates that organo-mineral associations can alternate between acting as phosphorus sinks and nutrient shuttles, depending on their saturation state and soil boundary conditions. Laboratory findings on mineral-associated organic matter cycling were further validated under field conditions investigating minerals buried in temperate grassland and forests for five years. Across all sites, goethite accrued nearly four times more carbon than illite, while the proportion of microbial biomass on mineral-associated organic carbon was higher on illite. Notably, carbon-, nitrogen-, and phosphorus-acquiring enzymes were significantly higher on goethite than illite or the surrounding soil, characteristic of microbial mining under nutrient limitations. Three overarching insights emerge. First, the amount of carbon stabilized on mineral surfaces is mineral-specific and further depends on molecular functionality and soil properties such as pH and phosphate accessibility, but no sorption-strength threshold dictates bioaccesibility. Second, microbial processing of mineral-associated organic carbon is inseparable from phosphorus cycling, both of which are mediated by mineral type. Third, oxides and clay minerals both contribute to the persistence of organic carbon, but via contrasting mechanisms. Illite´s nutrient-rich surfaces promote rapid turnover with high CUE that channels carbon into new biomass, whereas goethite traps larger amounts in forms less accessible to microbes, leaving the small bioavailable fraction prone to respiration. Together, these findings refine our understanding of how minerals govern organic matter turnover and nutrient availability in soil: their role is soil specific, affected by pH, nutrient availability, and land use.
Keywords: carbon cycling; mineral-associated organic matter; isothermal titration calorimetry; carbon use efficiency; carbon sequestration; ddc:333.7